Mechanism for Spatial Utilization Activity Compliance in Mining Business Licensing and Its Implications for Environmental Preservation - Ra’uf, Ardi Sirajudin; Imamulhadi; Adharani, Yulinda (Journal of Law, Politic and Humanities, 2026)
Indonesia's abundant natural resources, including the mining sector which contributes significantly to the country's economy, must be utilized carefully to preserve the environment. One of the main requirements for obtaining a business license is the Spatial Utilization Conformity Instrument (KKPR). The KKPR ensures that all business activities, including mining, can only be carried out in areas that are legally, ecologically, and spatially declared through digital verification of the RTRW and RDTR in the OSS system. This study aims to analyze the mechanism of spatial utilization activity compliance in mining business permits. This study uses a normative juridical approach, examining the rules, principles, and norms of positive law related to environmental preservation and the Mechanism of Spatial Utilization Activity Compliance (KKPR) in mining business licensing. Based on the results of the study, the KKPR mechanism in mining business permits is normatively designed as a spatial planning-based preventive instrument, but after the Job Creation Law, it tends to shift to an administrative instrument that depends on OSS and the availability of RDTR, thereby weakening its substantive control function. Furthermore, the implications of KKPR for environmental conservation have not been effective because assessments often ignore the carrying capacity and capacity of the environment, as reflected in the cases of mining on Sangihe Island and Trenggalek.